ENSURING ECONOMIC EFFICIENCY OF A PRICING POLICY IN THE SPHERE OF SERVICE OF A HEAT SUPPLY - O. V. Perchuk (Science and Innovation Center Publishing House, 2014)
In article the existing system of pricing in the sphere of thermal economy ofUkraineis considered, the order of formation of tariffs and their sizes are investigated. Major factors of influence on the price are defined and ways of improvement of existing system of pricing at the expense of economic and standard and legal levers are offered. Purchase on Elibrary.ru > Buy now